Meio ambiente no debate público: o discurso parlamentar bolsonarista na (re)construção do estado brasileiro - Hack, Wellington Felipe (2023)
This research is part of the interface of studies in Communication, Language and Philosophy, and it focuses on the relationship between Communication and State Theory from an environmental perspective. Methodologically supported by the contributions of Franco-Brazilian Discourse Analysis (AD), this research investigates the participation of the Bolsonarist discourse - from the Executive and Legislative branches - in the legitimation and (re)construction of the Social Contract of the Brazilian State in aspects related to the Environment. Thus, it is analyzed how the parliamentary Bolsonarism affects the public discussion about the Environment, from the study of the speeches made by former president Jair Bolsonaro and federal deputies aligned to the Federal Executive, and its incidence on the constitution of the Brazilian State. In order to achieve our main goal, we carried out this study based on three articulated movements. In order to structure this research, we discussed and approached the areas of knowledge in which it is based. In this way, we trace the theoretical referential in the tensioning of the place of Communication - especially journalism - in the constitution of the State. From the central concepts, we emphasize: the Social Contract, by Jean-Jacques Rousseau; the notion-concept of factual truth and the public debate from Hannah Arendt's perspective; and the concept of News from two points of view - as a form of knowledge, by Robert E. Park, and as a social form of knowledge in Adelmo Genro Filho. In a second movement, the Discursive Formations (DF) and the meanings in dispute about the environmental theme were identified in the discourse of the former president of Brazil and subject of the political-discursive Bolsonarist phenomenon, Jair Messias Bolsonaro. These discourses were taken as the voice of the Brazilian State before the United Nations General Assembly in 2019, 2020 and 2021, as well as the UN Climate Summit, also in 2021. After outlining the boundaries that govern the discursive formulations, we move on to look at the discursive materialities formulated in the Environment and Sustainable Development Commission of the House of Representatives in 2021. In answering our second specific objective, we present how the knowledges and senses in dispute are formulated in the defense of possible positions within the Bolsonarist movement. We analyze how some central elements of the Bolsonarist position are presented and reconfigured, strengthening the struggle for discursive hegemony about the agenda - as proposed by Ernesto Laclau. Finally, we structure an initial discussion about the role of journalism - especially the News - in the conformation of the Social Contract that forges the State. Thus, this study makes a special theoretical effort and contributes to think about the approximation of different fields of knowledge and to broaden the understanding of the role of journalism in the (re)construction of the Common.